Contextual inquiry and socio-technical practice. Issue 9 (28th October 2014) - Bednar, Peter; Elizabeth Welch, Christine
Abstract : Purpose: – During discussions at the ASC 2013 Conference, the authors were stimulated to consider acting, learning and understanding in the context of organizational change, and in particular the relationship between organizational actors and external analysts. The purpose of this paper is to review from a cybernetic perspective how a socio-technical toolbox can help to facilitate organizational change, and to examine issues involved in use of such a toolbox by organizational actors supported by expert analysts. Design/methodology/approach: – The paper is conceptual and adopts a critical stance, i.e. to provide support for emancipation of individuals through ownership and control of their own analyses. Findings: – Drawing on work by e.g. Bateson, the authors consider organizations as dynamic and complex human activity systems, and how actors can be helped to develop a productive learning "spiral" of acting and reflecting by means of a proposed socio-technical toolbox. Acting and reflecting upon action can be seen to form a "double helix" of learning, leading to richer understandings of contextual dependencies. Engaged actors need support to surface their contextually dependent understandings, individual and collectively and engage in a "dance of change". Practical implications: – Change is endemic in organizational life. When engaging with change activity that attempts to address complexity (as opposed to complicatedness), contextual experts need to be the key decision takers. This means a redistribution not only of responsibility and action but also decision-taking power. Originality/value: – The paper suggests augmentation of traditional socio-technical methods to address dynamic complexity.